Instruction of spirituality and spiritual care in nursing: A challenge in curriculum development - KhoramiMarekani, A; Yaghmaie, F; Izadi, A (Advances in Nursing & Midwifery, 2010)
Background and aim Spirituality as the essence of human existence and a healing factor in mankind has been increasingly emphasized in recent years. Spirituality along with three other domains of holistic care, namely biological, psychological and social has a particular importance.Holistic view provides a suitable approach for health professionals including nurses to focus on all aspects of human. World Health Organization (WHO), International Council of Nurses (ICN), ethical codes of universities worldwide and most theorists of nursing have emphasized on the instruction of spirituality and spiritual care in the frame of holistic approach. Since nurses are responsible to provide physical, psychological, social, cultural and spiritual care, they need to know how to respond to spiritual needs of their patients. This review article is intended to reveal the importance of spirituality and spiritual care instruction in nursing and focuses on legal as well as ethical requirements for its incorporation in educational planning as a challenge in baccalaureate nursing curriculum in Iran. Materials and methods A comprehensive review of literature in the Internet was performed to cover all material from 1980 to 2009. Keywords of the review included nursing, spirituality care education and spiritual care in domestic as well as international databases such as IranMedex, Irandoc, PubMed, ScienceDirect, ERIC, ProQuest and Ovid. Findings The review indicated that in most curriculums of western and eastern countries, instruction of spirituality and spiritual care is included; however, due to different reasons, nurses still do not have necessary preparations to identify and satisfy spiritual needs of their clients and require further academic education. In Iran, no study was found related to the necessity of inclusion of spirituality and spiritual care in the curriculum of baccalaureate nursing students. Conclusion Nursing educators play a critical role in the preparation of students to diagnose and satisfy clients’ spiritual needs. The principles of spirituality and spiritual care should be included and taught in the curriculum of the students. Keywords: Spirituality, Spiritual care, Nursing education, Curriculum. *Corresponding Author: Abdollah Khorami Markani, PhD Student, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Shariati, Tehran, Iran. E-mail: Khorami.Abdolah@gmail.com